Seroprevalence of COVID antibodies in health-care population of tertiary care government hospital in South India - Palanikumaran V; Vasantha Kalyani D; Suresh Kumar M; Fathhur Rabbani S; Natarajan M (Asian Journal of Medical Sciences, 2024)
Background: The pandemic coronavirus disease 2019 (COVID-19) caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in a worldwide abrupt and significant rise in admissions for pneumonia with multiorgan diseases. Aims and Objective: To determine the positive prevalence of SARS-CoV-2 antibodies in health-care professionals over 6 months. In addition, to make a subgroup analysis and estimate the age, gender, and workforce-based prevalence of SARS-CoV-2. Materials and Methods: An observational cross-sectional study was conducted on 200 healthcare professionals during 6 months. After taking proper informed consent, the study was started. We included subjects aged ≥18 years in this study. Not receiving any other vaccine during the study, suspected or confirmed immunosuppressive condition, imaging confirmed COVID-19 or recent blood transfusions were excluded from the study. Results: Most patients were 26–30 years old. Out of 200 patients, 116 (58%) were males, and 84 (42%) were females. The total positivity of the titers amounts was 57%. In addition, the males had higher mean titers than the females, with 24.186 versus 13.304. Of the 116 males, 68 were positive (58.6%), and of the 84 females, 46 were positive (54.7%). The age-wise positivity of the titers was high among the 26–30 years of age group, of which, in the 53 people, 33 were seropositive, which is 62.2% of this age group and lowest in the 51–55 years age group, of which in the 23 participants 9 were positive (39.31%), and 14 were negative (60.85%). Conclusion: We concluded that male doctors and adults had a greater seroprevalence of SARS-CoV-2 infection, suggesting that they are more susceptible to contracting COVID-19 through patient contact or surgical procedures.